A Changing Pattern of Brain-Derived Neurotrophic Factor Expression Correlates with the Rearrangement of Fibers during Cochlear Development of Rats and Mice - Wiechers, Barbara (J Neurosci, 1999)
The reorganization of specific neuronal connections is a typical feature of the developing nervous system. It is assumed that the refinement of connections in sensory systems requires spontaneous activity before the onset of cochlear function and selective sensory experience during the ensuing period. The mechanism of refinement through sensory experience is currently postulated as being based on the selective reinforcement of active projections by neurotrophins. We studied a presumed role of neurotrophins for rearrangement of afferent and efferent fibers before the onset of sensory function in the precisely innervated auditory end organ, the cochlea. We observed a spatiotemporal change in the localization of brain-derived neurotrophic factor (BDNF) protein and mRNA, which correlated with the reorganization of fibers. Thus, BDNF decreased in target hair cells during fiber retraction and was subsequently upregulated in neurons, target hair cells, and adjacent supporting cells concomitant with the formation of new synaptic contacts. Analysis of the innervation pattern in BDNF gene-deleted mice by immunohistochemistry and confocal microscopy revealed a failure in the rearrangement of fibers and a BDNF dependency of distinct neuronal projections that reorganize in control animals. Our data suggest that, before the onset of auditory function, a spatiotemporal change in BDNF expression in sensory, epithelial, and neuronal cells may guide the initial steps of refinement of the innervation pattern.